EFL Students' Perceptions towards the Use of MALL to Promote Students' Learning Autonomy - Bella Maharani Bhestari; Roghibatul Luthfiyyah (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2021)
The emergence of internet connections and digital mobile apps has caused a massive integration of Mobile-Assisted Language Learning (MALL) in English language teaching. Learners are fond to use MALL to practice their English proficiency inside and outside the classroom. Moreover, with the assistance of MALL features, learners can enhance their English competence as well as their learning autonomy. In this study, we intend to investigate perceptions of EFL students toward the use of MALL in English learning to promote their learning autonomy. Situated in a private university in Cirebon, this study voluntarily recruited four EFL students who have fulfilled a set of criteria to be involved in interview sessions and self-reflection. They are English students who have positive perceptions on technology acceptance and learning autonomy based on the data of a preliminary study. The findings show that participants perceived the ease of use and the usefulness of MALL applications in English learning. Besides, this study also reveals that participants agreed that MALL can support their learning autonomy outside the classroom. Some implications of the study are discussed further in this paper.